impact of Spinach (Spinacia oleraceae) , Omega3 and Zinc to reverse the fluoride induced hypothyroid in rats - Djouadi, Anfal (University Of Eloued جامعة الوادي, 2017)
The main goal of this study was to evaluate the phytotherapeutic impact based on the Spinach (Spinacia oleraceae) and also that of biotheraeutic based on the Omega3 and Zinc to reverse the fluoride induced experimental hypothyroid disease and its complications in rats. For this purpose, twenty four female albino Wistar rats were randomly divided into 6 groups (n=4); the first group used as a control group. Group II given fluoride as fluoride sodium (NaF) (400 ppm) to induce hypothyroidism. Group III hypothyroid rats given Spinach powder (17 g/kg) of diet. Group IV hypothyroid rats given Omega 3 as (1.825g Eicosapentaenoic acid (EPA)+1.21g docosahexaenoic acid (DHA)/kg) of diet. Group V hypothyroid rats given Zinc as ZnSO4,7H2O (0.230g/kg) of diet. Group VI hypothyroid rats given Spinach, Omega 3 and Zinc association. The exposure to fluoride for the hypothyroidism induction in rats is done during 70 days. As for the Spinach, Omega 3 and Zinc were added to the diet of the animals groups for last 15 days of hypothyroidism induction time. According to the results which have been obtained; there was an increase in serum TSH levels (70.53%) and a decrease in serum FT3 and FT4 levels (26.15% and 17.6%) respectively in hypothyroid group compared to the control. Results show also a significant (P<0.05) decrease in serum blood glucose, liver zinc and bone calcium levels and a significant (P<0.05) increase in lipid profile, electrolytes levels, markers of liver and renal functions in NaF induction of hypothyroidism group when compared to control rats. Moreover, the findings showed that hypothyroidism affected antioxidant defense system by decreasing Glutathione (GSH) level and Glutathione S transferase (GST) activity and increasing malondialdehyde (MDA) level in brain and kidney tissues. The histological examination of the cellular structure of the thyroid gland and kidney tissues of hypothyroid rats recorded changes in the follicular cells of the thyroid and in glomerulus and tubules of kidney tissues. However, the administration of Spinach, Omega 3 or Zinc alone ameliorated the thyroid function, biochemical parameters and restored the histological alterations while the combined treatment is the best improver for the thyroid dysfunction which had the totally restoring the biochemical parameters studied. In conclusion, present study demonstrated the beneficial effects of phytotherapy and biotherapy associated treatment on hypothyroidism and its metabolic and physiological complications.
Master
Keywords: Spinacia oleraceae; Omega3; Zinc; Hypothyroidism; Fluoride; السبانخ; أوميغا 3; زنك; قصور الغدة الدرقية; فلور